Activation of transcription in Drosophila embryos is a gradual process mediated by the nucleocytoplasmic ratio. - Pritchard, D.K.; Schubiger, G. (Genes & Development, 1996)
We have observed that zygotic transcription does not initiate at a single point in Drosophila embryos. Rather, a gene initiates transcription in a few nuclei of a fraction of embryos. During succeeding cycles, the frequency of transcribing embryos, and of nuclei transcribing in those embryos, gradually increases. For the fushi tarazu (ftz) gene, the timing of this process is regulated by the concentration of the maternally loaded, repressing transcription factor tramtrack (ttk). Altering the dose of Ttk protein in embryos shifts the activation of ftz transcription either forward or backward during development but does not effect Krüppel (Kr) activation. We have observed that the transcription of several genes, including ftz, is triggered in embryos at a critical nuclear density; therefore, we suggest that titration of transcription factors like ttk by the nucleocytoplasmic ratio triggers zygotic transcription in Drosophila.